Not all verbal labels grease the wheels of odor categories - Yaxiong Cao; Asifa Majid; Norbert Vanek (Language and Cognition)
Language is known to play a crucial role in influencing how humans perceive and categorize sensory stimuli, including odors. This study investigated the impact of linguistic labeling on odor categorization among bilingual participants proficient in Chinese (L1) and English (L2). We hypothesized that L1-like linguistic labels would more robustly propel the learning of new olfactory categories compared to a condition without language, and more familiar labels would better support odor category learning. The analysis focused on comparing learning trajectories and odor categorization performance of four groups, three in which odors were paired with different sets of verbal labels and a control group that categorized odors without any verbal labeling. Following four days of intensive training, the results showed that the groups with verbal labels numerically outperformed the control group, and that the less familiar the labels sounded the more successful categorization became. However, between-group differences did not reach statistical significance. These findings, while not conclusively supporting our hypotheses, provide insights into the complex relationship between linguistic familiarity and odor category formation. The results are nested within Ad Hoc Cognition, highlighting that variations in linguistic familiarity may not induce robust enough contextual changes to differentially affect how odor categories are formed.